THE WEFT OF TRUTH AND LIES AND ITS MISDEMEANOURS. ANALYSING THE ROLE AND SCOPE OF LIES IN ‟ABOUT ELLY” AND OTHER MOVIES OF ASGHAR FARHADI - Ioana CIOVÂRNACHE (Studia Universitatis Babeș-Bolyai. Philosophia, 2020)
The male and female, upper-class and lower-class, adult and child characters in Asghar Farhadi’s films remodel variants of the subject’s relationship to the Other. The intertwining of lies and truths into the subject’s fantasy or into the characters’ fictions sometimes (mis)leads the characters into violence, or brings them to face their subjective suffering, or, alternately, makes it possible for them to pass through their experience of mourning and to possible advance. The continuous shifting of the positions, value, perspectives and emotions has an unsettling effect upon the spectator’s subjective relation to the characters’ responsibility and actions.